A large topographic feature on the surface of the trans-Neptunian object (307261) 2002 MS4measured from stellar occultations - Rommel, F. L.; Braga-Ribas, F.; Ortiz, J. L.; Sicardy, B.; Santos-Sanz, P.; Desmars, J.; Camargo, J. I.B.; Vieira-Martins, R.; Assafin, M.; Morgado, B. E.; Boufleur, R. C.; Benedetti-Rossi, G. [UNESP]; et al. (EDP Sciences, 2023)
Context. The physical characterization of trans-Neptunian objects is essential for improving our understanding of the formation and evolution of our Solar System. Stellar occultation is a ground-based technique that can be successfully used to determine some of the TNOs-fundamental physical properties with high precision, such as size and shape. Aims. This work is aimed at constraining the size, shape, and geometric albedo of the dwarf planet candidate (307261) 2002 MS4 through the analysis of nine stellar occultation events. Using multichord detection, we also study the object-s topography by analyzing the obtained limb and residuals between the observed chords and the best-fit ellipse. Metods. We predicted and organized the observational campaigns of nine stellar occultations by 2002 MS4 between 2019 and 2022, resulting in two single-chord events, four double-chord detections, and three events with between 3 and 61 positive chords. We derived the occultation light curves using differential aperture photometry, from which the star ingress and egress instants were calculated. Using 13 selected chords from the 8 August 2020 event, we determined the global elliptical limb of 2002 MS4. The best-fit ellipse, combined with the object-s rotational information from the literature, sets constraints on the object-s size, shape, and albedo. Additionally, we developed a new method to characterize the topography features on the object-s limb. Results. The global limb has a semi-major axis of a′ = 412 ± 10 km, a semi-minor axis of b′= 385 ± 17 km, and the position angle of the minor axis is 121 ± 16. From this instantaneous limb, we obtained 2002 MS4-s geometric albedo of pV = 0.1 ± 0.025, using HV = 3.63 ± 0.05 mag and a projected area-equivalent diameter of 796 ± 24 km. Significant deviations from the fitted ellipse in the northernmost limb were detected from multiple sites, highlighting three distinct topographic features: One 11 km depth depression, followed by a 25-5+4 km height elevation next to a crater-like depression, with an extension of 322 ± 39 km and 45.1 ± 1.5 km deep. Conclusions. Our results indicate the presence of an object that is ∼138 km smaller in diameter than that derived from thermal data, possibly indicating the presence of a thus-far unknown satellite. However, within the error bars, the geometric albedo in the V-band is in agreement with the results published in the literature, even with the radiometric-derived albedo. This stellar occultation has allowed for the first multichord measurement of a large topography in a TNO.
Keywords: Kuiper belt objects: Individual: 2002 MS4; Methods: Observational